ARIMA MODELS UNTUK MEMPREDIKSI TINGKAT PERCERAIAN DI LOMBOK TIMUR - Lina Septia Hultafiana Maziyyah; Wiwit Purwa Nurmayanti; Muhammad Malthuf (Journal of Applied Statistics and Data Mining, 2020)
Selong Religious Court Office is one office whose duties take care of various cases, one of which is divorce cases. Divorce inEast Lombok changes every year. Based on data from Selong Religious Court, divorce annually in East Lombok increased. Tofind out whether divorce matters in two the coming year will experience an increase as well or rather has decreased then ananalysis of time series (forecasting) with using the ARIMA (Autoregressive Integrated Moving Average) method. The aim is tofind out which time series model is right for forecasting divorce rates and also to find out how many results from divorceforecasting in East Lombok Regency 2020-2021. Based on the analysis results got that the best model is ARIMA (3,1,3) with anMSE value of 220.6. From the forecasting results it is known that the total number of divorce predictions for 2020 are January(124), February (984), March (100), April (123), May (96), June (104), July (122), August (93), September (107), October (120),November (92), December (111). Whereas forecasting for 2021 is January (118), February (91) March (114), April (115), May(91), June (117), July (112), August (91), September (119) , October (108), November (93), December (121).